The CITI Program: An alternative to train Latinoamerica in investigation's ethics - Litewka, Sergio; Goodman, Kenneth; Braunschweiger, Paul (Acta Bioethica, 2008)
The CITI Program (Collaborative Institutional Training Iniciative) is a course based on Internet with no profit intention: it has been developéd by volunteers who offer educational subjects on human beings' protection in biomedical investigations, as will as on conduct, good medical practices, responsible conduct in investigation and humanitarian behaviour towards laboratory animals. This Program is a joint effort done by the Fred Hutchinson Cancer Research Centre and the University of Miami. With the collaboration of local experts a considerable part of its content has been adapted for Latin America, is has been translated to Spanish and Portuguese and collaborative agrees have been established with bioethics' specialized institutions in Chile, Brazil, Costa Rica and Peru. Its authors present an accessible methodology in order to train on investigation's ethics and to justify ins use and spreading out throughout Latin America.